Cotton GhSSI2 isoforms from the stearoyl acyl carrier protein fatty acid desaturase family regulate Verticillium wilt resistance. (24th June 2021) - Mo, Shaojing; Zhang, Yan; Wang, Xingfen; Yang, Jun; Sun, Zhengwen; Zhang, Dongmei; Chen, Bin; Wang, Guoning; Ke, Huifeng; Liu, Zhengwen; Meng, Chengsheng; Li, Zhikun; et al.
Abstract: Lipids are major and essential constituents of plant cells and provide energy for various metabolic processes. However, the function of the lipid signal in defence against Verticillium dahliae, a hemibiotrophic pathogen, remains unknown. Here, we characterized 19 conserved stearoyl‐ACP desaturase family proteins from upland cotton ( Gossypium hirsutum ). We further confirmed that GhSSI2 isoforms, including GhSSI2‐A, GhSSI2‐B, and GhSSI2‐C located on chromosomes A10, D10, and A12, respectively, played a dominant role to the cotton 18:1 (oleic acid) pool. Suppressing the expression of GhSSI2 s reduced the 18:1 level, which autoactivated the hypersensitive response (HR) and enhanced cotton Verticillium wilt and Fusarium wilt resistance. We found that low 18:1 levels induced phenylalanine ammonia‐lyase‐mediated salicylic acid (SA) accumulation and activated a SA‐independent defence response in GhSSI2 s‐silenced cotton, whereas suppressing expression of GhSSI2 s affected PDF1.2‐dependent jasmonic acid (JA) perception but not the biosynthesis and signalling cascade of JA. Further investigation showed that structurally divergent resistance‐related genes and nitric oxide (NO) signal were activated in GhSSI2 s ‐ silenced cotton. Taken together, these results indicate that SA‐independent defence response, multiple resistance‐related proteins, and elevated NO level play an important role in GhSSI2 s ‐ regulated Verticillium wilt resistance. These findings broaden our knowledge regarding the lipid signal in disease resistance and provide novel insights into the molecular mechanism of cotton fungal disease resistance. Abstract : GhSACPD gene family isoforms GhSSI2‐A, GhSSI2‐B, and GhSSI2‐C displayed an important role in regulating 18:1 fatty acid level and negatively regulated cotton disease resistance to Verticillium wilt.